2020
DOI: 10.13106/jafeb.2020.vol7.no2.309
|View full text |Cite
|
Sign up to set email alerts
|

Social Responsibility, Organizational Commitment, and Organizational Performance: Food Processing Enterprises in the Mekong River Delta

Abstract: This study aims to measure the relationship between corporate social responsibility (CSR) and affective commitment (ACO), normative commitment (NCO), and organizational performance in food processing enterprises (FPEs) in the Mekong River Delta, Vietnam. To test the initial model proposed in this paper, a total of 422 owners, directors and managers of FPEs were interviewed from some provinces in the Mekong River Delta. The method of exploratory factor analysis (EFA) is initially employed, then confirmatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
0
23
0
5
Order By: Relevance
“…Arup (2005) suggested that employees in the collective culture judge highly the value of organizational hierarchy and have a greater need to connect and support (nurture), always seek the support of direct managers (Restubog, Bordia, Tang, & Krebs, 2010) and need more protection and guidance than employees working in Western culture (Anand, S., Vidyarthi, P. R., Liden, R C., Rousseau, 2010). As employees receive encouragement and care from direct supervisors, this not only increases the organization commitment, it also improves operational performance (Nguyen & Tu, 2020)normative commitment (NCO.…”
Section: Discussionmentioning
confidence: 99%
“…Arup (2005) suggested that employees in the collective culture judge highly the value of organizational hierarchy and have a greater need to connect and support (nurture), always seek the support of direct managers (Restubog, Bordia, Tang, & Krebs, 2010) and need more protection and guidance than employees working in Western culture (Anand, S., Vidyarthi, P. R., Liden, R C., Rousseau, 2010). As employees receive encouragement and care from direct supervisors, this not only increases the organization commitment, it also improves operational performance (Nguyen & Tu, 2020)normative commitment (NCO.…”
Section: Discussionmentioning
confidence: 99%
“…It is also an individual's psychological engagement to that organization, by which the attachment to organization, acceptance and transformation of the organization's values and goals into employee's and behavioral effort to support organization are recognized (Judge & Kammeyer-Mueller, 2012). Organizational commitment is a psychological relation between employee and his organization that helps to constraint the employee's ability to quit current job (Nguyen & Tu, 2020).…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…CSR, sometimes referred as corporate ethics, corporate responsibility, and citizenship, is a broad complex concept and continually evolving. In the past, CSR was considered an obligation of the firm to society (Huynh et al, 2020;Nguyen & Tu, 2020;Smith, 2003). Then, today CSR is a voluntary activity done by organizations in order to bring benefit to workforce and community.…”
Section: Literature Reviewmentioning
confidence: 99%